2009
DOI: 10.1016/j.archoralbio.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microarchitectural changes in a mouse temporomandibular joint osteoarthritis model

Abstract: Objective-Little is known about the natural progression of the disease process of temporomandibular joint (TMJ) osteoarthritis (OA), which affects approximately 1 % of the US population. The goal of this study was to examine the early microarchitectural and molecular changes in the condylar cartilage and subchondral bone in biglycan/fibromodulin (Bgn/Fmod) doubledeficient mice, which develop TMJ-OA at 6 months.Methods-TMJs from 3 month old (n=44) and 9 month old (n=52) wild-type (WT n=46) and Bgn/ Fmod (n=50) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Six studies applied in vivo micro-CT, performed in the maxilla [6], [15], [20], [21] and in the condyle [10], [22]. The scanning device which was most often used was the μCT 40 (Scanco Medical, Brüttisellen, Switzerland) [9], [11], [13], [14], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], followed by the Skyscan apparatus (Skyscan, Aartselaar, Belgium) [3], [4], [8], [20], [21], [32], [33], [34], [35]. The results of the quantitative analysis are presented in Table 2, Table 3, Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies applied in vivo micro-CT, performed in the maxilla [6], [15], [20], [21] and in the condyle [10], [22]. The scanning device which was most often used was the μCT 40 (Scanco Medical, Brüttisellen, Switzerland) [9], [11], [13], [14], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], followed by the Skyscan apparatus (Skyscan, Aartselaar, Belgium) [3], [4], [8], [20], [21], [32], [33], [34], [35]. The results of the quantitative analysis are presented in Table 2, Table 3, Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3 papers investigated the effect of forced mouth opening on mandibular condyle structure, in both male and female rats [26], [28], [45]. Two longitudinal studies [10], [22] on condylar micro-architectural changes in response to experimental interventions such as osteoporosis and occlusal loading were retrieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulate that these early alterations of extracellular matrix components lead to biomechanically compromised chondro-osseous tissue which is then susceptible to later stage damage by loading forces that occur during joint use. The validity of this argument is strengthened by studies of biglycan and fibromodulin single and double knock-out mouse models which show age dependent cartilage biomechanical changes with histologic and clinical features of osteoarthritis [21][22][23]. In addition, human genetic association studies have identified polymorphisms in other single extracellular matrix genes such as COMP [24], OPN [25], and SDC4 [26] which appear to predispose individuals to late-stage osteoarthritis [27].…”
Section: Discussionmentioning
confidence: 99%
“…The SAMP3 strain shows not only an early and high incidence of severe degeneration in the TMJ, but these changes start at three months of age 6) . One of the severe pathological changes in TMD is a destruction of the joint cartilage, known as osteoarthritis (OA), which is characterized by degradation and erosion along the surface of articular cartilage 7) and results in changes to the subchondral bone structure 8) .…”
Section: Introductionmentioning
confidence: 99%